Dynamic single-photon emission computed tomography as a method of identification of multivessel coronary artery disease - A. V. Mochula; K. V. Zavadovsky; S. L. Andreev; Yu. B. Lishmanov (Вестник рентгенологии и радиологии, 2016)
Objective. The aim of this study was to determine the informative value of dynamic tomoscintigraphy in detection of multivessel coronary artery disease (CAD).Material and methods. Patients with multivessel CAD (n= 16) and healthy volunteers (n= 9) underwent dynamic cardiac single photon emission computed tomography with 99mТс-MIBI at rest and during pharmacological stress-test.Processing of acquired results involved the formation of regions of interest from the cavity and the myocardium of the left ventricle used to create activity-time curves. Coronary flow reserve index was defined as a quotient of two ratios of the mean counts from the myocardial region to the integral activity in the left ventricular cavity for the studies performed during pharmacological stress test and at rest.Results. The mean values of coronary flow reserve index were 1.86 (1.59; 2.2) in group of healthy volunteers and 1.39 (1.12; 1.69) in patients with multivessel CAD. When the value of this index was less than 1.77, the method allowed for detection of three-vessel CAD with the sensitivity and specificity rates of 81.8% and 66.7%, respectively.Conclusion. Performing the standard myocardial perfusion scintigraphy in combination with the method of coronary flow reserve index assessment allows for enhancement of the diagnostic value of scintigraphic approach in the evaluation of coronary circulation disturbances in multivessel CAD.